2009
DOI: 10.2174/157489109789318569
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Pyrazoline Derivatives -A Recent Development

Abstract: Pyrazolines are well known and important nitrogen containing 5-membered heterocyclic compounds and various methods have been worked out for their synthesis. Numerous pyrazoline derivatives have been found to possess considerable biological activities, which stimulated the research activity in this field. They have several prominent effects, such as antimicrobial, antimycobacterial, antifungal, antiamoebic, anti-inflammatory, analgesic, antidepressant and anticancer activities. They also possess some potent rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 34 publications
0
98
0
1
Order By: Relevance
“…64 In another two studies conducted individually it was observed that pyrazoline derivatives derived from phenoxy acetic acid had higher anti-viral activity against a broad panel of viruses in different cell cultures. 65,66,67 Another such constituent structure having anti-viral activity was diphenylmethane of Progabide (DB00837). Intriguingly, diphenylmethane and its derivatives are active against a host of viral infections like Bovine-viral diarrhoea virus, A-PR8 virus, poliomyelitis virus, adenovirus, vaccinia virus and MHV3 virus.…”
Section: Discussionmentioning
confidence: 99%
“…64 In another two studies conducted individually it was observed that pyrazoline derivatives derived from phenoxy acetic acid had higher anti-viral activity against a broad panel of viruses in different cell cultures. 65,66,67 Another such constituent structure having anti-viral activity was diphenylmethane of Progabide (DB00837). Intriguingly, diphenylmethane and its derivatives are active against a host of viral infections like Bovine-viral diarrhoea virus, A-PR8 virus, poliomyelitis virus, adenovirus, vaccinia virus and MHV3 virus.…”
Section: Discussionmentioning
confidence: 99%
“…They have signi cant biological activities including antimicrobial, anticonvulsant and antiviral [5][6][7][8][9]. The asymmetric unit of the title structure contains one molecule, in which the phenyl ring (C10-C15) is highly deviated from the whole molecule plane and makes a dihedral angle of 78.74(3)°with the pyrazol ring (N1-N2-C7-C8-C9).…”
Section: Discussionmentioning
confidence: 99%
“…Signal 7 which splitted as triplet predicted as proton of aromatic ring 3 in C 3 which had two protons neighbor. Proton 7 and 8 that had integration of 2 protons were protons from aromatic ring 3 . From 1 H-NMR spectra, it could be said that pyrazoline has been formed.…”
Section: Synthesis Of Pyrazolinementioning
confidence: 99%
“…Pyrazole and pyrazoline are important nitrogen containing 5-membered heterocyclic compound. Pyrazoline which is well known as pyrazole derivative or 4,5-dihydropyrazole is reported possess a broad spectrum of biological activities such as anticonvulsant [2], antimicrobial [1,3,8], antiamoebic [3], analgesic [1], anti-inflammmatory [1], antidepressant [4], anxiogenic [4], inhibitors of monoamine oxidase [4], fungisical [5], insecticidal [5], antitumor [6], and antinociceptive [7]. Therefore, the prevalence of pyrazole core in biologically active molecules has stimulated the need for elegant and efficient ways to make these heterocyclic lead.…”
Section: Introductionmentioning
confidence: 99%